Management Practices and Feed Supplements on the Growth of Two Chicken Breeds (Gallus Domesticus L.) under Smallholders’ Farm Conditions: Case of Rajshahi - Islam, M. Saiful; Mustari, Sharmin (ABC Journal of Advanced Research, 2017)
The present study assessed the management practices and feed supplements on growth performance of two common chicken breeds viz., Fayoumi (an exotic) and Sonali (a crossbred) in 10 Upozillas or Police Stations of Rajshahi District. For the collection of experimental data every week, a government, 10 private and 10 backyard smallholders’ poultry farms were selected, and the investigation was conducted from January to December 2015. Fourteen such major management practices as feeding, vaccination, bio-safety measures, disposal of wastes and dead bodies were considered to rank the farms from excellent (score 5) to unacceptable (score 1) scales. All the parameters showed significant variation (P<0.05) except room heating, source of water, bio-safety measures, contacts with veterinarians, disposal of excreta, access of wild animals and disease management. The second half of the survey witnessed a relatively better management practices in all farm types. Results on feed supplements and growth performance of both sexes of Fayoumi and Sonali chickens up to 8 weeks with four dietary treatment groups viz., T1 (control), T2 (control + 12500 IU vitamin A (VitA)/kg feed), T3 [control + essential amino acids (EAAs)] and T4 (control + 12500 IU VitA/kg feed + EAAs) were promising. Feed conversion ratios (FCR), survivability (SB%) and carcass characteristics (CC) exhibited treatment effects (P<0.001) but no breed effect with respect to FCR. Conversely, gender effect showed significant variation for all the CC (P<0.05) except for breast meat. In contrast, dressing yield, drumstick meat and thigh meat had no treatment effects. It appeared from the present results that strict bio-safety oriented management practices, coupled with the selection of fast growing and heavy laying breeds of chickens and feed supplements at recommended doses could ensure sustainability as well as profitability of the emerging poultry farms in the study area.